Community Structure of Macroalgae in the Coastal Waters of Bahowo - Tamara, Giovanni Matthew A. J.; Kepel, Rene Charles; Lumingas, Lawrence J. L.; Wantasen, Adnan S.; Lasabuda, Ridwan; Lohoo, Anneke V. (Jurnal Ilmiah PLATAX, 2025)
This research aims to describe the morphology and anatomy of each species from the research location and to analyze the community structure of macroalgae from the research location. Data collection was done using the Line Transect method with a quadrat sampling technique during the lowest tide. Temperature and salinity checks were measured using a thermometer and refractometer. Substrate determination was done visually based on the type of substrate. The results of this study found 9 species, consisting of 4 red algae species (Rhodophyceae) and 5 green algae species (Ulvophyceae). The morphology of these algae species varies, with different anatomy based on transverse and longitudinal sections of each part of the alga's thallus. The highest species density was H. edulis, while the lowest densities were A. fragilissima, D. versluysii, T. fragilis, and C. racemosa. The macroalgae diversity index values in the three transects are in the medium category, the species evenness index values are stable, the species richness index values are in the low category, and the dominance index values are in the low category. Keywords: Macroalgae, Community, Transect, Quadrat, Bahowo.   Abstrak Tujuan penelitian ini adalah mendeskripsikan morfologi dan anatomi masing-masing spesies dari lokasi penelitian, dan menganalisis struktur komunitas makroalga dari lokasi penelitian. Pengambilan data menggunakan metode Line Transect dengan teknik sampling kuadrat yang dilakukan pada saat surut terendah. Pengecekan suhu dan salinitas diukur dengan menggunakan termometer dan refractometer. Untuk penentuan substrat dilihat secara visual terhadap jenis dari substrat tersebut. Hasil penelitian ini ditemukan 9 spesies yang terdiri dari 4 spesies alga merah (Rhodophyceae), dan 5 spesies alga hijau (Ulvophyceae). Morfologi jenis-jenis alga tersebut beragam dengan anatomi yang berbeda berdasarkan potongan melintang dan memanjang dari masing-masing bagian thallus alga. Kepadatan spesies tertinggi yaitu H. edulis sedangkan kepadatan terendah yaitu A. fragilissima, D. versluysii, T. fragilis, dan C. racemosa. Nilai indeks keanekaragaman makroalga pada ketiga transek termasuk dalam kategori sedang, nilai indeks kemerataan jenis dalam keadaan stabil, nilai indeks kekayaan jenis dalam kategori rendah dan nilai indeks dominasi dalam kategori rendah. Kata kunci: Makroalga, Komunitas, Transek, Kuadrat, Bawoho